The sounds of fighting: contests between violet vinegar crabs, Episesarma versicolor (Tweedie, 1940) (Decapoda: Brachyura: Sesarmidae), are resolved through acoustic communication - Goh, Song Lin Rigel (Oxford University Press (OUP), 2019)
Journal of Crustacean Biology